2021
DOI: 10.3390/ph14090880
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Effects of Curcumin against Influenza Using In Silico and In Vitro Approaches

Abstract: The influenza virus is a constantly evolving pathogen that challenges medical and public health systems. Traditionally, curcumin has been used to treat airway inflammatory diseases, such as bronchitis and pneumonia. To elucidate common targets of curcumin and influenza infection and underlying mechanisms, we employed network pharmacology and molecular docking approaches and confirmed results using in vitro experiments. Biological targets of curcumin and influenza were collected, and potential targets were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…A recent study reported that curcumin inhibited SARS-CoV-2 D614G strain by pre-infection treatment of Vero E6 cells [ 12 ]. This effect has also been observed with other enveloped viruses including IVA [ 13 , 14 ]. Previous studies have reported that curcumin prevents SARS-CoV-2 entry by direct interaction with cell factors or viral proteins [ 15 , 16 ].…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…A recent study reported that curcumin inhibited SARS-CoV-2 D614G strain by pre-infection treatment of Vero E6 cells [ 12 ]. This effect has also been observed with other enveloped viruses including IVA [ 13 , 14 ]. Previous studies have reported that curcumin prevents SARS-CoV-2 entry by direct interaction with cell factors or viral proteins [ 15 , 16 ].…”
Section: Introductionsupporting
confidence: 72%
“…Plants are the major source for new drug discoveries to combat infectious disease [ 11 ]. Among these, curcumin is a promising candidate as it shows antiviral activity against both SARS-CoV-2 and IVA [ 12 , 13 ]. A recent study reported that curcumin inhibited SARS-CoV-2 D614G strain by pre-infection treatment of Vero E6 cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The whole IAV genome codes for different proteins including NA (neuraminidase), RNA polymerases (PB1, PB2, and PA), HA, M1 (matrix proteins), M2 (ion channel), and NP (nucleoprotein) (Hutchinson, 2018). In silico studies targeting NA, PB2, HA, M1, and M2, as well as different signaling pathways (AKT1, TP53, MAPK1, and RELA) illustrated that curcumin and its different derivatives act as acceptable inhibitors of these proteins and pathways (Jayasree et al, 2014; Kim, Choi, Kim, Kang, & Kim, 2021b; Richart et al, 2018; Roy et al, 2021; Satpathy et al, 2012; Singh & Misra, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In uenza virus is an evolving pathogen that is a serious threat to medical and public health systems (14).…”
Section: Discussionmentioning
confidence: 99%